KONTRIBUSI PONDOK PESANTREN DALAM MENGEMBANGKAN HUMAN CAPITAL - Niam, Muh.; Adi, Isbandi Rukminto (Jurnal Pembangunan Manusia, 2021)
The development of Islamic boarding schools in Indonesia has been transformed not only as an Islamic educational Institution (tafaqquh fiddin), but also as a Faith-Based Organization (FBO) which is engaged in the social, economic, and the surrounding social community. Developing human capital as one of the strategies in social development and has become one of the forms of activities that can be carried out by Islamic boarding schools to the surrounding community, activities in the community also become one of the forms of dakwah bil hal in the community. This Research discussed the contribution of Roudlotun Nasyi’in Ash Shiddiqiyyah (RN ASA) Islamic boarding school as FBO in developing human capital, which is the purpose of this research. A qualitative approach was used in this research. Data collection using in-depth interviews was conducted with 19 selected informants who were composed of Kyai, students and administrators, and members of the boarding school or local community. Documentation studies and observations were also carried out on several activities in the community in developing human capital carried out by RN ASA Islamic boarding school. Based on the results of this research has known that the contribution of RN ASA Islamic boarding school as FBO in developing human capital was shown through skills training and moral development of students and surrounding communities. Skills training consists of making kerupuk uyel, making wallets and handicrafts, while moral development is done an educational approach. Based on the results of the research was known that the boarding school RN ASA in developing human capital has touched students and administrators of boarding schools, and the surrounding community. The development of human capital implemented by RN ASA boarding school has touched and given a chance in developing the aspects of education, morals, social, and economics of the community around the RN ASA.